Contribuição ao conhecimento da flora do Aripuanã (Mato Grosso) II. Musci - Lisbôa, Regina Célia Lobato; Lisbôa, Pedro Luiz Braga (Acta Amazonica, 1978)
A lista of species of Musci from Aripuanã, State of Mato Grosso, Brazil, is given. The material listed was collected during the month of October (1975) and first trimester of 1977. 17 families, 26 genera and 44 species were collected. The families with the largest number of individuals were: Sematophyllaceae, Leucobryaceae, Calymperaceae. Thuidiaceae, Meteoriaceae and Plagiotheciaceae. All the families collected are typical of Tropical climate and they have all been previously recorded in the State of Amazonas except for the Hydropogonaceae, which is a new record for the State. The most common species were: Thuidium involvens and Sematophyllum subsimplex. Notes on habitats and substrates are given for each species.